Role of masonry fabric subsurface moisture on biocolonisation. A case study. (15th February 2022) - Prieto, B.; Young, M.E.; Turmel, A.; Fuentes, E.
Abstract: High moisture is one of the main factors favouring the growth of algae and other organisms on stone surfaces. However, little is known about the specific effects of subsurface moisture on this process. Some regions will be exposed to longer periods of humidity and rainfall as a result of climate change. Understanding the role and internal dynamics of moisture in stone is therefore essential to enable development of mechanisms for controlling biological colonisation and thus preventing biodeterioration. The present case study is a preliminary investigation of the role of subsurface moisture in the biocolonisation process and was conducted on the walls of the Guard House of Stirling Castle. Moisture was measured at depth (up to 3, 11 and 30 cm) in both interior and exterior walls of the building with a portable device based on non-destructive microwave technology. Data were analysed in relation to the orientation of the walls, type of stone and biocolonisation. The subsurface moisture between 3 and 11 cm was found to play an important role in supporting colonising organisms on the building by modulating bioreceptivity. Highlights: Biocolonisation is modulated by subsurface moisture in the building envelope. Moisture studies on building envelope should consider depth and amount of subsurface moisture. Moisture content of stone is the main factor determining bioreceptivity but is regulated by surface roughness.